Analisis Kesuksesan Implementasi E-Kinerja di Kota Salatiga Menggunakan Model DeLone-McLean - Manora, Elsa; Maria, Evi; Chernovita, Hanna Prillysca (Building of Informatics, Technology and Science (BITS), 2021)
The Agency for Personnel and Human Resources Development (BKPSDM), Salatiga City, implements e-Kinerja to analyze job requirements, job workloads and units or work units, as a basis for calculating work performance and awarding awards. BKPSDM has never measured the success of using e-Kinerja. The purpose of this research is to evaluate the implementation of e-Kinerja in BKPSDM, Salatiga City using the DeLone-McLean model. E-Kinerja users in BKPSDM, Salatiga City are a sample of this research. The total sample was 66 respondents. The questionnaires were measured using Likert Scale and testing was conducted using the Pearson Product Moment Correlation method. Research obtained empirical evidence that successful implementation of e-Kinerja plays a role in improving performance in BKPSDM. The research findings are also robust in additional testing. The average weight of the measurement item, which is 4.04 and the success rate of e-Kinerja implementation is 80.8 percent. E-kinerja successful in improving job performance in BKPSDM, Salatiga City.